The Role of Formyl Peptide Receptors in Neurological Diseases via Regulating Inflammation - Zhu, Jiahui; Li, Lingfei; Ding, Jiao; Huang, Jinyu; Shao, Anwen; Tang, Bo (Frontiers in Cellular Neuroscience, 2021)
Formyl peptide receptors (FPRs) are a group of G protein-coupled cell surface receptors that play important roles in host defense and inflammation. Owing to the ubiquitous expression of FPRs throughout different cell types and since they interact with structurally diverse chemotactic agonists, they have a dual function in inflammatory processes, depending on binding with different ligands so that accelerate or inhibit key intracellular kinase-based regulatory pathways. Neuroinflammation is closely associated with the pathogenesis of neurodegenerative diseases, neurogenic tumors and cerebrovascular diseases. From recent studies, it is clear that FPRs are important biomarkers for neurological diseases as they regulate inflammatory responses by monitoring glial activation, accelerating neural differentiation, regulating angiogenesis, and controlling blood brain barrier (BBB) permeability, thereby affecting neurological disease progression. Given the complex mechanisms of neurological diseases and the difficulty of healing, we are eager to find new and effective therapeutic targets. Here, we review recent research about various mechanisms of the effects generated after FPR binding to different ligands, role of FPRs in neuroinflammation as well as the development and prognosis of neurological diseases. We summarize that the FPR family has dual inflammatory functional properties in central nervous system. Emphasizing that FPR2 acts as a key molecule that mediates the active resolution of inflammation, which binds with corresponding receptors to reduce the expression and activation of pro-inflammatory composition, govern the transport of immune cells to inflammatory tissues, and restore the integrity of the BBB. Concurrently, FPR1 is essentially related to angiogenesis, cell proliferation and neurogenesis. Thus, treatment with FPRs-modulation may be effective for neurological diseases.